Epidemiological study of American Tegumentary Leishmaniasis (ATL) in Northeastern Brazil (Research, Society and Development, 2020)
American Cutaneous Leishmaniasis (ATL) is an infectious, non-contagious disease that causes ulcers on the skin and mucous membranes. The disease is caused by protozoa of the genus Leishmania. The disease is transmitted to humans by the bite of infected female sand flies (species of fly). The present study aimed to quantify and analyze the reported cases of ATL in the Northeast. It was a documentary, retrospective, descriptive research with a quantitative approach. The notified cases of ATL were collected from the Informatics Department of the Unified Health System (DATASUS) having the following variables studied: year, sex, type of entry, clinical form, etiological classification and evolution. Between 2014-2018, 23,767 cases of ATL were reported in the Northeast. Analyzing these cases, by year of notification, the following percentage distribution was obtained: 2014 (23%), 2015 (23%), 2016 (16%), 2017 (21%), 2018 (18%). There was a significant difference between females (63%) and males (37%). It was observed that the type of entry per new case (93%) and the cutaneous clinical form of the disease (96%) prevailed. All notified cases were classified as imported (100%). Regarding the evolution of the cases, the cure was presented as the main outcome (59%). The epidemiological study made it possible to know the aspects of ATL in the Northeast. The study also demonstrates the importance of compulsory notification forms as an instrument that allows assessing the epidemiological profile of cases of ATL as well as providing subsidies for structuring control measures that should be incorporated and prioritized to combat the disease.